Breastfeeding in the first six months of life for babies seen by Lactation Consulting - Bruna Alibio Moraes; Juliana Karine Rodrigues Strada; Vanessa Aparecida Gasparin; Lilian Cordova do Espirito-Santo; Helga Geremias Gouveia; Annelise de Carvalho Gonçalves (Universidade de São Paulo, 2021)
Objective: to identify breastfeeding patterns, survival of exclusive breastfeeding and factors associated with its interruption, in the first six months of life of babies seen by Lactation Consulting. Method: a prospective cohort, with 231 mother-babies in a Baby-Friendly Hospital. An initial questionnaire was applied after 24 hours of birth, after consulting, as well as a follow-up questionnaire, applied by telephone at 15, 30, 60, 120 and 180 days, with sociodemographic and obstetric variables, maternal habits, father's schooling, birth data and baby feeding. Survival Analysis was carried out. Results: at 180 days of age, exclusive breastfeeding was 12.7% and the probability was 19.6% in the analysis of the survival curve. The factors associated with its interruption were smoking during pregnancy (HR 1.66; CI 1.05 - 2.61), age ≥ 35 years old (HR 1.73; CI 1.03 - 2.90), difficulty in breastfeeding after hospital discharge (HR 2.09; CI 1.29 - 3.41), search for professional assistance (HR 2.45; CI 1.69 - 3.54) and use of a pacifier (HR 1.76; IC 1.21 - 2.58). Conclusion: lactation consultancy contributed to the improvement of the exclusive breastfeeding rates, although there are opportunities for advances.